Gut microbiota and obesity - Božić Antić, Ivana; Vojnović Milutinović, Danijela (Medicinski podmladak, 2025)
Obesity represents a multifactorial, systemic disorder strongly associated with adverse health outcomes, including cardiometabolic syndrome. Beyond caloric imbalance between caloric intake and expenditure, recent evidence highlights the essential role of gut microbiota in the development and progression of obesity and related metabolic dysfunctions. The gut microbiota, composed of diverse bacterial species, archaea, fungi, and viruses, influences host metabolism through the production of low-molecular-weight metabolites and gastrointestinal hormones, significantly modulating energy homeostasis, appetite regulation, and insulin sensitivity. Specific bacterial taxa are implicated in either promoting metabolic health or contributing to obesity through mechanisms involving chronic systemic low-grade inflammation, increased intestinal permeability, and altered energy harvest. Dysbiosis—marked by reduced microbial diversity and compositional imbalance—is consistently linked to enhanced adiposity and systemic inflammation. Dietary patterns are key modulators of gut microbial composition and function. This review underscores the complex interplay between dietary patterns, gut microbiota-derived metabolites and host endocrine responses, that contribute to dysregulation of gut–brain axis communication observed in obesity.